Factors influencing the improvement of self-management behavior in hemodialysis patients - Mohamad Jebraeily; Khadijeh Makhdoomi (Society of Diabetic Nephropathy Prevention, 2018)
Introduction: Hemodialysis (HD) patients encounter several challenges. They require strong attention to behavioral and lifestyle changes. Objectives: The purpose of this study was identifying factors that influence the improvement of self-management behavior in a group of HD patients. Patients and Methods: This is a cross-sectional survey conducted with participation of 420 patients in HD centers in Urmia University of Medical Sciences in 2017. For data collection, a self-designed questionnaire was designed. Results: The most important factors which are effective to improve self-management behavior were related to psychosocial support (4.66), patient education and empowerment programs (4.58), religious beliefs (4.50), active participation of family members (4.43), expanding role providers for self-management patient (4.36), and patient literacy and readiness (4.30) respectively. Conclusion: For the promotion of self-management behavior, healthcare providers should increase the abilities of patients for disease management. Therefore, it seems that selfmanagement training for HD patients is a crucial element of the care process.